A study of Lumpy skin disease outbreak in Thi Qar Province - Ahmed N. Fayad (University of Thi-Qar Journal of Science, 2019)
In this study the clinical diagnosis of lumpy skin disease was depended. A total 1606 serum samples and skin biopsies collected from infected cows clinically with skin nodule of different size which change to a necrotic nodule or form a deep scab, from wide different areas and cities of Thi Qar , extended from June to November at 2016.      ELISA were performed for identification of LSDV antibodies, LSDV isolation was carried out on CAM of ECE  and Viral DNA was extracted from skin biopsy for PCR.     All serum samples was show seropositivity against LSD. Isolation of LSD virus from skin biopsy was conducted on CAM and the isolated virus was identified by PCR. collection and processing of clinical samples, viral isolation and PCR assay, for LSDV are much sensitive and rapid diagnostic of LSD their importance in controlling the rapid spread of disease in Iraq.